Los dilemas del sindicalismo en Nicaragua / Roland Membreǫ Segura, Holguer Cisneros, Mario Martínez Caldera - Cisneros, HolguerMartínez Caldera, Mario; Membreǫ, Roland
Datos tomados de la cub.Precede al tít.: Solidarismo